Preservation of a Rare Art, Okokan, through the Quality Improvement in Musical Instrument Quality and Merchandise Design - Swandi, I Wayan; Julianto, I Nyoman Larry; Mudra, I Wayan (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
An Okokan art group named "Omelan I Kayu Bolong" in Banjar Dinas Kukuh Kangin, Kukuh Village, Kerambitan District, Tabanan Regency, is a partner in the implementation of the Community Partnership Program (CPP). The issues of the partner are that the musical instruments for the Okokan performance have been dull, and the paint has peeled off. Meanwhile, the partner had no merchandise to promote this Okokan art group. CPP aims to improve the capability of this art group, revitalize the Okokan musical instrument by re-coating ornaments, and design merchandise. CPP was implemented with the training to be attended by the partners, which started with a Focus Group Discussion and continued with training for coating the Okokan ornament and designing the merchandise. The CPP improved the partner's skill in re-coating the Okokan musical instrument and merchandise design as the media for promotion, in the form of Okokan miniature, logo, poster, and T-shirt.